Adobe Photoshop CC 2014 release - Faulkner, Andrew; Gyncild, Brie (Classroom in a book, 2015)
Adobe Photoshop CC Classroom in a Book contains 14 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. In addition to learning the key elements of the Photoshop interface, this completely revised CC (2014 release) edition covers new features, including Generator, 3D printing, linked Smart Objects, Blur Gallery, smarter Smart Guides, Perspective Warp, and more.